Analisis Pengelolaan Penjualan Penyambung (Entres) Kopi Berdasarkan Penerapan Social Oriented, Kebun Induk Kopi Robusta, Desa Sai, Kecamatan Pupuan - Luh Gede Kusuma Dewi; Umbu Joka (Fakultas Pertanian, Universitas Timor, 2020)
This study aims to: 1) To find out the background of Robusta Coffee Estate, Sai Village, Pupuan Subdistrict, selling coffee connoisseurs based on the application of Social Oriented; 2) To find out the characteristics and advantages of the Robusta Coffee Main Estate; and 3) To find out whether the sales of coffee connectors can achieve social oriented operations at the Robusta Coffee Estate operations, Sai Village, Pupuan District. This type of research is a qualitative study with research subjects, namely the Head of the Horticultural Agriculture Service Unit and Staff at the Robusta Coffee Estate. Data obtained in this study were collected through interviews, observations, documentation and literature studies. The results of this study indicate: 1) Background of Sales of Coffee Entres in Coffee Parent Farms is to provide coffee entres used by farmers in revitalizing their unproductive coffee plants; 2) Characteristics and Advantages of Application of Social Oriented is to improve the social life of the community so that it can improve the welfare of life through coffee farming activities; And 3) Sales of Oriented Social-Based Coffee Entres on Robusta Coffee Plantation Operations Activity is to set the selling price into two, specifically community coffee farmers at a price of Rp250 / section and project activities / Community Economic Institutions at a price of Rp750 / segment.